Management of Acquired Hemophilia A in Elderly Patients - Yamaguchi, Tomoya; Kudo, Naoko; Endo, Susumu; Usui, Takeo; Imashuku, Shinsaku (Case Reports in Hematology, 2018)
This report describes six elderly patients with acquired hemophilia A (AHA), including four individuals aged ≥90 years. Bleeding symptoms were subcutaneous or intramuscular hemorrhage (n=4), hematuria (n=1), and hemorrhagic shock after tooth extraction (n=1). Factor VIII (FVIII) activity ranged from <1.0% to 3.0%, and anti-FVIII inhibitor titers ranged from 8.8 to 240 BU/mL. Treatment was administered at the discretion of the responsible physician. Hemostatic agents applied in the six patients comprised rFVIIa (NovoSeven®) (n=4), APCC (Feiba®) (n=2), and fresh frozen plasma/plasma exchange (n=1). Agents employed for inhibitor eradication comprised prednisolone only (n=3), prednisolone with cyclophosphamide (n=1), prednisolone with cyclosporine (n=1), and prednisolone with rituximab (n=1). In five patients, management was successful, with complete response. Treatment failed in the patient with the highest inhibitor level (240 BU/mL) in whom treatment with APCC (Feiba®; 100 U/kg/dose, three doses) and prednisolone (0.5 mg/kg/day) was followed by several episodes of relapse. The present data demonstrate that AHA severity shows wide variation in elderly subjects, indicating the necessity of individualized management.